2021
DOI: 10.1007/s00261-021-03085-w
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics of hepatocellular carcinoma: promising roles in patient selection, prediction, and assessment of treatment response

Abstract: Radiomics refers to the process of conversion of conventional medical images into quantifiable data ("features") which can be further mined to reveal complex patterns and relationships between the voxels in the image. These high throughput features can potentially reflect the histology of biologic tissues at macroscopic and microscopic levels. Several studies have investigated radiomics of hepatocellular carcinoma (HCC) before and after treatment. HCC is a heterogeneous disease with diverse phenotypical and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Recently, there has been a significant increase in radiomics investigations, including in the liver field: liver fibrosis assessment, characterization of malignant and benign lesions, and prognosis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a significant increase in radiomics investigations, including in the liver field: liver fibrosis assessment, characterization of malignant and benign lesions, and prognosis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that radiomics features could characterize the tumor and its tumor microenvironment (TME) [36][37][38][39][40][41][42], and were closely related to specific microscopic features at genes, proteins, and molecular levels. Radiomic features have been suggested in the application of predicting molecular subtyping, tumor gene expression, pathological classification, treatment response, and survival [38][39][40][41][42][43][44]. Deep learning is a class of machine learning techniques that can extract a large number of higher-level deep features from deep hidden layers of convolution neural network (CNN), which has been widely adopted in image recognition and image classification.…”
Section: Introductionmentioning
confidence: 99%
“…In radiomic analysis, a statistical model is constructed to predict clinical events, such as prognosis or response. In clinical practice, radiomics technology is widely used to determine the prognosis of HCC [ 33 , 34 ]. One prediction model was established using preoperative enhanced CT images and machine learning, which can accurately predict the preoperative pathological grade of liver cancer [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%